Rice (Oryza sativa L.) production, productivity, and harvested area in Karawang Regency under extreme weather from 1991-2023 - Buswar, Adine Syabina; Ruminta, Ruminta; Wicaksono, Fiky Yulianto (Kultivasi, 2025)
Climate change occurred in Karawang Regency due to extreme weather events, which are included in the El Nino climate anomaly phenomenon. The existence of extreme weather events in Karawang Regency has decreased rice production, which is a climate-dependent crop. Based on this problem, a study was conducted to analyze the identification of extreme weather changes and correlation analysis of rice crops in Karawang Regency to see the magnitude of extreme weather changes and the influence of extreme weather elements on rice crops. The method used is a quantitative descriptive method by analyzing extreme weather changes, correlation analysis of extreme weather elements on rice plants (production, productivity, and harvest area), and correlation graphs of extreme weather elements with rice plants. Data was obtained from BPS, BMKG, and the Karawang Regency Agriculture and Food Security Office. The results showed that Karawang Regency experienced extreme weather changes due to climate change, namely an increase in the average maximum rainfall (1.78 mm), an increase in maximum temperature (0.76 °C), a decrease in minimum temperature (-0.57 °C), a decrease in wet spell for 3 days, and an increase in dry spell for 10 days. The impact of extreme weather change, namely the wet spell element, has a real significant correlation with a moderate level to a decrease in rice production and productivity.